AN ANALYSIS OF MARKETING EFFICIENCY OF BEEF CATTLE BREEDERS PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY, NORTH SUMATERA - Sakral Hasby Puarada; Riris Nadia Syafrilia Gurning (RADJA PUBLIKA, 2022)
The livestock business is a business consisting of fattening and breeding. Cows are one of the food producers that have a lot of value and nutrition. The high economic value is in line with the increase in population, and the need for food consumption in Indonesia continues to increase every year. Therefore, we must be able to cope with the increasing demand for meat. One of these needs is raising cattle or animal feed and understanding the livestock supply chain as seen from the decline in livestock and feed prices in the market. Knowledge of supply chain flow and beef cattle marketing efficiency is an alternative solution to ongoing problems. The research location is in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, considering that Percut Sei Tuan District is one of the sub-districts that runs a beef cattle business. This study aims to see how the efficiency of beef cattle marketing. The method used is measuring marketing efficiency and looking at the farmer's share in the beef cattle supply chain. From the study results, it was found that the marketing efficiency analysis of each of the beef cattle supply chain actors in this study has reached a high level of efficiency starting from suppliers, farmer groups and retailers.